2011
DOI: 10.2220/biomedres.32.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hericium erinaceus on amyloid β(25-35) peptide-induced learning and memory deficits in mice

Abstract: The mushroom Hericium erinaceus has been used as a food and herbal medicine since ancient times in East Asia. It has been reported that H. erinaceus promotes nerve growth factor secretion in vitro and in vivo. Nerve growth factor is involved in maintaining and organizing cholinergic neurons in the central nervous system. These findings suggest that H. erinaceus may be appropriate for the prevention or treatment of dementia. In the present study, we examined the effects of H. erinaceus on amyloid β(25-35) pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 26 publications
(42 reference statements)
5
45
0
1
Order By: Relevance
“…106 Evaluation of the learning function of the mice by behavioral pharmacological methods (Y-maze and novel-object recognition tests) indicates that the mushroom powder improves the cognitive deficits induced by the amyloid peptide, suggesting that the powder might be a promising treatment for cognitive dysfunction. Additional HPLC studies showed that the powder contained the following three hericenones: C, 4.12 mg/g; D, 0.21 mg/g; and E, 0.49 mg/g.…”
Section: ■ Anticarcinogenic Propertiesmentioning
confidence: 99%
“…106 Evaluation of the learning function of the mice by behavioral pharmacological methods (Y-maze and novel-object recognition tests) indicates that the mushroom powder improves the cognitive deficits induced by the amyloid peptide, suggesting that the powder might be a promising treatment for cognitive dysfunction. Additional HPLC studies showed that the powder contained the following three hericenones: C, 4.12 mg/g; D, 0.21 mg/g; and E, 0.49 mg/g.…”
Section: ■ Anticarcinogenic Propertiesmentioning
confidence: 99%
“…In traditional Chinese medicine, HE has long been considered a medicinal mushroom, and it was reported that effective compounds such as threitol, β-sitosterol, (1) and pyrone compounds. (2) HE also reported which might have prevention of cognitive dysfunction, (3) modulation of lipid metabolic gene expression, (4) stimulation nerve growth factor synthesis, (5,6) and anti-cancer activity. (7,8) We hypothesized that HE could protect against oxidative damage by scavenging reactive oxygen species (ROS) such as superoxide anion and hydroxyl radicals, and its fraction might be useful for anti-inflammatory effect in RAW 264.7 macrophages.…”
Section: Introductionmentioning
confidence: 97%
“…In mice, dietary supplementation with H. erinaceus prevents the impairment of spatial short-term and visual recognition memory induced by amyloid β (25–35) peptide [2]. Recently, Hazekawa et al [3] described the neuroprotective effects of H. erinaceus dietary supplementation in mice subjected to middle cerebral artery occlusion.…”
Section: Introductionmentioning
confidence: 99%